2021
DOI: 10.1002/ps.6095
|View full text |Cite
|
Sign up to set email alerts
|

Nematicidal activity of teleocidin B4 isolated from Streptomyces sp. against pine wood nematode, Bursaphelenchus xylophilus

Abstract: BACKGROUND Pine wilt disease (PWD) is a plant disease that causes serious damage to pine trees. PWD occurs when the host plant is infected with pinewood nematode (PWN), Bursaphelenchus xylophilus. In this study, a compound with nematicidal activity was isolated from actinomycetes and its efficacy was investigated in vitro. RESULT We screened and selected Streptomyces sp. 680560, which had nematicidal activity against B. xylophilus. Based on 16S rRNA sequence analysis, it showed 99.93% similarity with Streptomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…GLL‐9 had excellent inhibitory effects against both Xcc and P. italicum , while its ethyl acetate extract (EAE) had an even greater inhibitory effect with MIC values of 31.25 ( P. italicum ) and 62.50 (Xcc) μg mL −1 . According to previous reports, the secondary metabolites from Streptomyces species had inhibitory effects on several plant pathogens and could act as biological control agents against many agricultural pests 47,48 . It was reported that the primary microorganism responsible for the production of antibiotics is Streptomyces 49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GLL‐9 had excellent inhibitory effects against both Xcc and P. italicum , while its ethyl acetate extract (EAE) had an even greater inhibitory effect with MIC values of 31.25 ( P. italicum ) and 62.50 (Xcc) μg mL −1 . According to previous reports, the secondary metabolites from Streptomyces species had inhibitory effects on several plant pathogens and could act as biological control agents against many agricultural pests 47,48 . It was reported that the primary microorganism responsible for the production of antibiotics is Streptomyces 49 .…”
Section: Discussionmentioning
confidence: 99%
“…According to previous reports, the secondary metabolites from Streptomyces species had inhibitory effects on several plant pathogens and could act as biological control agents against many agricultural pests. 47,48 It was reported that the primary microorganism responsible for the production of antibiotics is Streptomyces. 49 The Streptomyces species was widely used for the production of some antibiotics such as rapamycin 50 and avermectin, 51 and both of them were effective in controlling pests and diseases in agricultural crops.…”
Section: Discussionmentioning
confidence: 99%
“…Compound 240 was toxic toward B. xylophilus and affected egg hatching. 100 Chaetoglobosin A (ChA) 241 was isolated from Chaetomium globosum NK102; it exhibited adverse effects on the vitality of M. incognita , and significantly inhibited J2 penetration. 101 Compound 241 and chaetoglobosin B 242 were obtained from the endophytic strain C. globosum YSC5; both caused mortality of the J2 of M. javanica , with LC 50 values of 88.4 and 107.7 μg mL −1 after 72 h, respectively.…”
Section: Structures and Nematicidal Activitymentioning
confidence: 99%
“…14,19,20 Natural products have been an important source for the development of new drugs and agrochemicals not only because of their diverse structures and biological activities but also because of their multiple modes of action and environmentally friendly characteristics. 7,21 Nowadays, usually avermectin and its derivative emamectin benzoate have been used for the prevention and treatment of B. xylophilus and Meloidogyne. 22−24 Jietacins (Figure 1) are a kind of natural product that were isolated from the fermentation broth of Streptomyces sp.…”
Section: ■ Introductionmentioning
confidence: 99%